Parental Decision-Making on Childhood Vaccination - Damnjanović, Kaja; Graeber, Johanna; Ilić, Sandra; Lam, Wing Y.; Lep, Žan; Morales, Sara; Pulkkinen, Tero; Vingerhoets, Loes (Frontiers in Psychology, 2018)
A growing number of parents delay vaccinations or are deciding not to vaccinate their children altogether. This increases the risk of contracting vaccine-preventable diseases and disrupting herd immunity, and also impair the trust in the capacities of health care systems to protect people. Vaccine hesitancy is related to a range of both psychological and demographic determinants, such as attitudes towards vaccinations, social norms, and trust in science. We focus on parents and our aim is to understand those determinants, because they are a special group in this issue – proxy decision makers – as they are deciding for their children, who are unable to do so themselves. The fact that deciding to vaccinate is a socially forced choice that concerns a child’s health makes vaccine-related decisions highly important and involving for parents. This high involvement might lead to parents overemphasizing the potential side effects that they know to be vaccine-related, and by amplifying those, parents are more focused on the potential outcomes of vaccine-related decisions, which can yield specific pattern of the outcome bias. We propose two related studies to investigate factors which promote vaccine hesitancy, protective factors that determine parental vaccination decisions, and outcome bias in parental vaccination intentions. We will explore demographic and psychological factors, and test parental involvement related to vaccine hesitancy using an online battery in a correlation panel design study. The second study is an experimental study, in which we will investigate the moderating role of parents’ high involvement in the specific domain of vaccination decision making. We expect that higher involvement among parents, compared to non-parents, will shape the pattern of the proneness to outcome bias. The studies will be conducted across eight countries in Europe and Asia (Finland, Germany, Hong Kong, the Netherlands, Serbia, Slovenia, Spain, and the United Kingdom), rendering findings that will aid with understanding the underlying mechanisms of vaccine hesitancy and paving the way for developing interventions that are custom-made for parents.